2018
DOI: 10.3390/socsci7120244
|View full text |Cite
|
Sign up to set email alerts
|

Female Genital Mutilation in Nigeria: A Persisting Challenge for Women’s Rights

Abstract: Although considered a violation of human rights, female genital mutilation (FGM) is a commonly accepted practice in Nigeria in the ritual and sociocultural context of the population. In recent years, there have been strong policy actions by Nigerian legislature to curb this practice. Despite that, FGM continues to be a widespread phenomenon. In this study, we aimed to report on the prevalence of FGM, women’s attitude towards this practice, and its association with selected sociodemographic factors. Methods: Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…As demonstrated in other studies, women in rural areas were more likely to be subjected to FGM than those in urban areas [12] as urban women would be more educated and informed about the harms of this practice. Like other authors [5,[24][25][26], educational attainment was a protective factor against female genital mutilation in Benin according to the 2011-2012 DHS; thus women who had no education were the most frequently cut. Our study showed, as did the study conducted by Karmaker et al [28], that compared to women practicing traditional religion or voodoo, Muslim women were more likely to be circumcised, although no religion prescribes this practice [29].…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…As demonstrated in other studies, women in rural areas were more likely to be subjected to FGM than those in urban areas [12] as urban women would be more educated and informed about the harms of this practice. Like other authors [5,[24][25][26], educational attainment was a protective factor against female genital mutilation in Benin according to the 2011-2012 DHS; thus women who had no education were the most frequently cut. Our study showed, as did the study conducted by Karmaker et al [28], that compared to women practicing traditional religion or voodoo, Muslim women were more likely to be circumcised, although no religion prescribes this practice [29].…”
Section: Discussionsupporting
confidence: 50%
“…The underlying assumption in the choice of sociodemographic variables was that female genital mutilation, as a contradictory practice, persists in some social groups because of either a lack of adequate information about adverse effects or a preference for adherence to traditional values of health and well-being. A common misconception was that some households chose not to deviate from the established social norm for fear of the high social costs that could result from non-compliance [5]. Cultural and ethnic practices that are potentially harmful to health are generally more prevalent among "lower" socio-economic status communities who are also less likely to acquire health knowledge [19].…”
Section: Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Scholars have highlighted the possibility that social norms could be driving FGM/C in Senegal (Kandala and Shell-Duncan 2019). In addition, research efforts have been directed to increased understanding of contextual determinants of FGM/C and the distribution of the practice across communities and regions over time (Achia 2014;Yaya and Ghose 2018;Kandala and Shell-Duncan 2019). However, no study has so far assessed the linkage between geographical location, individualand community-level factors, and FGM/C among girls, using the most recent datasets available for Senegal.…”
Section: Introductionmentioning
confidence: 99%